More about nationalism than geopolitics - Demko, Atilla (2022)
What led to the war in Ukraine is not just the country’s drive for NATO and EU membership. Other Central and Eastern European nations joined both organisations suffering only verbal protest from Russia. The war in Ukraine is about much more than cold geopolitics; it is a war between Russian and Ukrainian nationalism.